Dorotheus of Gaza and Benedict of Nursia - Egender, Nikolas (Cistercian studies quarterly, 2009)
The article discusses the views of Christian monks Dorotheus of Gaza and Benedict of Nursia on Christian unity. Dom Lucien Regnault commended Dorotheus for his integral practice of the coenobitic form of life that is not restricted by contemplative orientation. Pastor W. Wissert Hooft stressed the principle of the ecumenical method of drawing nearer to Jesus Christ as similar to the beliefs of Dorotheus.